Studies of intrinsically curved and forcibly curved DNA as well as their interactions with topological enzymes - Yang, Zhaoqi (2012)
Topological enzymes, both type I and type II topoisomerases, are not only essential for the processes of cell growth, but also for their effect on altering the geometrical conformations of DNA. It has been shown that Human topoisomerase I (hTopo I), belonging to the type I subfamily, binds to DNA in a topology-dependent fashion with a strong preference for supercoiled DNA over relaxed DNA. Furthermore, it has been reported that eukaryotic topoisomerase I acts preferentially on intrinsically curved DNA. Prior to thoroughly investigating the mode of action of hTopo I, the specific structure of the substrate had to be identified. A series of forcible curved circular DNA (cDNA) structures were prepared, in order to investigate a particular recognizable characteristic of hTopo I. All of the cDNAs exhibited more efficient interference to hTopo I-catalyzed plasmid relaxation, than linear duplex DNA. The half maximal inhibitory concentration (IC50) can be modulated by the curvature degrees of cDNA. In addition, the preferential binding of hTopo I to cDNA containing high curvature has been demonstrated by atomic force microscopy (AFM) and electrophoretic mobility shift assay (EMSA). The results of this research suggest that hTopo I can preferentially recognize the curved conformation of cDNA. Moreover, hTopo I has been known as a potential target for cancer therapy, as a consequence of its crucial role in replication and transcription. Accordingly, hTopo I can preferentially recognize the forcible curvature in cDNA and act preferentially on the intrinsically curved DNA. A series of duplex DNA structures, with different intrinsic curvatures, has been designed as inhibitors to hTopo I. The activity of hTopo I in relaxing supercoiled pUC 19 is apparently diminished in the presence of the curved DNA. More potent inhibitions and smaller IC50 values are achieved by duplex DNA with higher curvatures. These studies demonstrate that the activity of hTopo I can be modulated by the intrinsic curvature of linear DNA. Moreover, these results can be used to provide a new method to design curved DNA as hTopo I inhibitors with high therapeutic efficiency and low toxicity.